2016
DOI: 10.6000/1929-6029.2016.05.04.3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about the Health Effects of Passive Smoking among Bangladeshi Young Adults

Abstract: Passive smoking is now firmly established as a significant cause of morbidity and mortality. Assessment of young adults’ perceptions, understanding and knowledge of the health effects of passive smoking may promote educational endeavours to increase awareness of the passive smoking-linked health effects and to facilitate interventions. The study, therefore, assessed the perceptions of young adults in Bangladesh about the health effects of passive smoking. This cross-sectional descriptive study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The current study find out most of them (85.7%) are live in nuclear family and only 14.3% were lives in extended family. Similar result was found in a study conducted by Sultana et al, (2016) [6], they found that most of the participants lives in nuclear Another study also found similar report. Majority of the participants (94.6%) were lived in nuclear family and 5.4% single parent family [19] in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The current study find out most of them (85.7%) are live in nuclear family and only 14.3% were lives in extended family. Similar result was found in a study conducted by Sultana et al, (2016) [6], they found that most of the participants lives in nuclear Another study also found similar report. Majority of the participants (94.6%) were lived in nuclear family and 5.4% single parent family [19] in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…Students tend to be more susceptible to secondhand smoking related harm because of secondhand smoking exposure in the environment [5]. A large number of adult people and children are affected by secondhand smoking from their own home or in other public place [6]. School children are exposed to Secondhand smoking through living with smoker indoor at homes, open public places as like where selling pan, tobacco and a ban on smoking, work places, public transport, in child care centers, kindergartens or pre-schools, open boundary space of schools, in all areas of train stations, covered bus shelters, raised platform tram stops and all tram stop shelters [7].Tobacco smoke release 4,000 chemicals, among them 250 chemicals are identified in secondhand smoke, and 50 of them chemicals are known carcinogens [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the prevalence of smoking among university students in Bangladesh is 60.2%, thus, increasing the likelihood of exposure to SHS 27 . Currently, there is a lack of understanding and awareness on the adverse effect of SHS 28 . Although SHS exposure in Bangladesh has been strongly linked with gender, age, literacy, household incomes, and number of smokers in the family 29 , the adverse consequences of secondhand smoking on university students’ sleep quality have remained an under-investigated area in the country’s public health landscape.…”
Section: Introductionmentioning
confidence: 99%